Sediment Suspended Concentration (SSC) Profile in Padang River Estuary Area Bandar Khalifah Sub District Serdang Bedagai Regency North Sumatera Province - Hutapea, Yeru Daniel Octryan; Rifardi, Rifardi; Elizal, Elizal (Fakultas Perikanan dan Kelautan Universitas Riau, 2019)
SSC (Sediment Suspended Concentration) is the concentration of suspended sediment. This research was conducted in June 2018 in the Muara Sungai Padang area, Bandar Khalifah District, Serdang Bedagai Regency, North Sumatra Province. This research aims to describe the distribution of vertical and horizontal SSC suspended sediments and the factors that influence them in Padang river estuary area, Bandar Khalifah District, North Sumatra Province. The method used in this research is the survey method and determining the location of sampling by purposive sampling. Measurement of water quality parameters is carried out in situ, namely temperature, salinity, pH, depth, current speed, and brightness. The results of the study of the distribution of suspended sediments in the waters of the Padang river can be concluded that the pattern of the distribution of suspended sediments when the tide moves towards the upper reaches of the river while at low tide moves towards the sea, namely the waters of the Malacca Strait which is influenced by currents. the largest suspended sediment concentration at tide to low tide is at the sampling point 1 which is 179 mg / l and recedes to pairs at sampling point 1 which is 121 mg / l.